Universities and the Production of Elites Discourses, Policies, and Strategies of Excellence and Stratification in Higher Education - Bloch, Roland; Mitterle, Alexander; Paradeise, Catherine; Peter, Tobias (Palgrave Studies in Global Higher Education, 2018)
XI, 392 p. 10 illus.